1990
DOI: 10.1111/j.1365-2141.1990.tb02542.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of warfarin on plasma concentrations of vitamin K dependent coagulation factors in patients with stable control and monitored compliance

Abstract: There is a discrepancy in the results of reported studies of levels of vitamin K dependent coagulation factors in patients on warfarin therapy. This may have arisen partly because of the problem of assuring compliance with therapy in outpatients. The plasma concentrations of the vitamin K dependent clotting factors II, VII, IX and X were studied in 23 outpatients whose adherence to prescribed warfarin therapy was determined using a pharmacological indicator of compliance. In these patients, who were shown to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 17 publications
3
6
1
Order By: Relevance
“…Similar findings were also reported in 50 patients (Lind et al, 1997). In another study of 23 patients on long-term therapy, the levels of FII and FX were depressed to a significantly lower level than those of FVII and FIX (Kumar et al, 1990). The evidence from several studies suggests that the depletion of FII, and to a lesser extent FX, is crucial for the success of clinically effective oral anticoagulation, as well as its bleeding complications.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar findings were also reported in 50 patients (Lind et al, 1997). In another study of 23 patients on long-term therapy, the levels of FII and FX were depressed to a significantly lower level than those of FVII and FIX (Kumar et al, 1990). The evidence from several studies suggests that the depletion of FII, and to a lesser extent FX, is crucial for the success of clinically effective oral anticoagulation, as well as its bleeding complications.…”
Section: Discussionsupporting
confidence: 80%
“…A decrease in vitamin K-dependent factor levels in patients on long-term coumadin therapy has been found to be quite variable in several studies (Paul et al, 1987;Kumar et al, 1990;Lind et al, 1997). In a study of 37 patients, Paul et al (1987) found that FX levels were the lowest, FII levels intermediate and FVII and FIX levels the highest.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation studies revealed an disproportionate prolongation of the admissions APTTs, which was found to be caused by a strong and excessive decrease of FIX:C to 1-3% (Table I, plasma sample 1). Usually, during oral anticoagulant therapy FIX:C is decreased to a similar degree or remains even higher than the activity of the other vitamin K dependent factors (Kumar et al, 1990;Weiss et al, 1987). Therefore our patients were believed to have mild haemophilia B, which was exacerbated due to phenprocoumon administration.…”
Section: Discussionmentioning
confidence: 90%
“…Both coumarins function as vitamin K antagonists, decreasing the activities of the vitamin K dependent procoagulant components prothrombin, factor VII, IX, X and also of the coagulation inhibitors protein C and protein S. The kinetics of decrease of the vitamin K dependent factors depends on their specific half-lives and on the dose of the oral anticoagulant drug (Weiss et al, 1987;Kumar et al, 1990). The decrease is induced by a competitive interference of coumarins with enzymes of the vitamin K cycle (Hirsh, 1991).…”
mentioning
confidence: 99%
“…The PT assays differ in types of throm boplastin and dilution which also greatly in fluence their sensitivity and the influence of the protein induced by vitamin K absence inhibitor [2], however, identical results can be obtained by standardization [3], It is believed, at present, that PT reflects all vitamin In dependent coagulation factors [4][5][6][7] except factor IX [8,9],…”
Section: Introductionmentioning
confidence: 99%